Investigation of far-infrared (FIR) optical behaviors in ferroelectric (FE)-semiconductor film - Ramli Abdul Wahab
This study is for investigates the behavior of the second - order transition ferroelectric (FE) film under the influence of illuminating far - infrared (FIR) ray.